EVALUASI MODEL BISNIS PETERNAK LELE DESA BANGKOK DENGAN PENDEKATAN BISNIS MODEL CANVAS - Muhamad Puad Zaqa Sauqi Fataqi (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Pokdakan Sumber Rejeki is a group of fish farmers in Bangkok village that was founded in 2017. In order to run a business well, a good plan is needed. Canvas business is one method for managing business so that it can be carried out properly. The purpose of this research is to provide an analysis and evaluation of the application of the business model carried out by Pondakan Sumber Rejeki on the basis of a study using the canvas business model theory. The analysis used is qualitative analysis with in-depth interviews in collecting primary data with descriptive writing characteristics. The results of this study are making evaluation of Pokdakan Sumber Rejeki's business by paying more attention to the management of the organizational structure which focusses on development of knowledge and technology. Hopefully, the evaluation of this research can improve the benefit and development of Pokdakan Sumber Rejeki.